KONSISTENSI PEMBENTUKAN PERATURAN DAERAH BERDASARKAN HIERARKI PERUNDANG-UNDANGAN DALAM PRESPEKTIF POLITIK HUKUM - Aristo Evandy A. Barlian (Fiat Justisia: Jurnal Ilmu Hukum, 2016)
AbstractThe local government is an extension of the central government to run the government in order to achieve the purpose of the state. In order to realize effective regional governance and harmonious required local regulations in line with the substance of the material, human rights, public interest and does not conflict with other regulations thereon. Until the end of 2016 recorded over 3000 local regulations that was rejected by the Minister of the Interior, where the process of making regulations clearly very nominal spending of state finances. There are forms of relationship communication, consultation, clarification drafts are applied between Government agencies with the authorities in the area for less than effective, in addition to the optimization of the minimal role of the Governor and Members of the Board in developing and overseeing the regional administration is one of the factors that make local regulation do not have a clear substance and in accordance with usefulness. Disharmony between central government and local governments are also an important factor which the step coaching is done by the agency Centre for local government apparatus in the preparation of the Regulation is still said to be not optimal and equitable then not their frame of reference is clear to the area of the administration of the harmonization of the draft law as an instrument important in order to maintain the harmonization of laws with other regulations. Law No.12 of 2011 has had signs which point to the importance of harmonization of rules including local regulations. Article 5 defines a rule that is considered good if it has met the principle of legislation such as clarity of purpose, the fit between the type and material content, usefulness and clarity of the formulation. The draft local regulation harmonization with other rules above areas should be supported by clear and firm rules and to always be integrated as a formal requirement of drafting local regulations as stipulated in Presidential Regulation No. 61 of 2005 which regulates the process of harmonization, rounding, and stabilization of the conception of the regulation draft in Indonesia. Keywords: Consistency Local Regulation, Hierarchy Regulatory and Political of Law. AbstrakPemerintah daerah merupakan perpanjangan tangan dari pemerintah pusat untuk menjalankan roda pemerintahan guna mencapai tujuan bernegara. Dalam mewujudkan pemerintahan daerah yang efektif dan harmonis diperlukan peraturan daerah yang sejalan dengan substansi materi, hak asasi manusia, kepentingan umum dan tidak bertentangan dengan peraturan lain diatasnya. Sampai akhir 2016 terdata lebih dari 3000 Perda yang ditolak oleh Menteri Dalam Negeri dimana proses pembuatan perda jelas sangat menghabiskan nominal keuangan negara. Terdapat bentuk hubungan komunikasi, konsultasi, klarifikasi Raperda yang diterapkan antara instansi Pemerintah dengan aparat di daerah yang selama ini masih kurang efektif, selain itu optimalisasi yang minim dari peran Gubernur dan Anggota Dewan dalam membina dan mengawasi penyelenggaraan pemerintahan kabupatan/kota adalah salah satu faktor yang menjadikan Perda tidak memiliki substansi yang jelas dan sesuai dengan kemanfaatannya. Disharmonisasi antara pemerintah pusat dan pemerintah daerah juga merupakan faktor penting di mana langkah pembinaan yang dilakukan oleh instansi pusat kepada aparatur pemerintah daerah dalam penyusunan Perda masih dikatakan belum optimal dan merata serta tidak adanya kerangka acuan yang jelas bagi daerah mengenai tata laksana harmonisasi Raperda sebagai salah satu instrumen penting dalam rangka menjaga harmonisasi Perda dengan Peraturan lainnya. UU No.12 Tahun 2011 telah memiliki rambu-rambu yang mengarahkan pada pentingnya harmonisasi PUU termasuk Perda. Pasal 5 UU tersebut menentukan PUU dinilai baik apabila telah memenuhi asas peraturan perundang-undangan seperti kejelasan tujuan, kesesuaian antara jenis dan materi muatan, kedayagunaan dan kejelasan rumusan. Harmonisasi Raperda dengan PUU perlu didukung oleh aturan yang jelas dan tegas serta senantiasa dintegrasikan sebagai syarat formal penyusunan Perda sebagaimana tertuang dalam Peraturan Presiden No. 61 Tahun 2005 yang mengatur proses mengenai pengharmonisasian, pembulatan, dan pemantapan konsepsi pada draft rancangan undang-undang di Indonesia. Kata kunci: Konsistensi Peraturan Daerah, Hierarkhi Perundang-undangan, dan Politik Hukum